VARIABILITY OF PHRASEOLOGICAL UNITS IN ENGLISH AND SEMANTIC PROBLEMS IN TRANSLATION - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2021)
This article aims to reveal the lexical-semantic features of phraseological units in English and determine their emotional-expressive features. Furthermore, one of the main goals of this article is to illustrate semantic analysis in translation as there are some difficulties in consequence of meaning differences.